Prevalence of Cryptosporidium Oocysts In Different Types of Water in Al-Mansoria Diala Province - Al-Baytee, Ahmed J; Jawad, Shatha Q; Mehdi, Hadi S (Al-Nahrain Journal of Science, 2018)
The aim of the present study was to evaluate the prevalence of Cryptosporidium oocysts, and the importtance of the water source in the prevalence of Cryptosporidium spp. Four types of water samples (400 L.s.) .100 Ls .tap water supplies, 100 L.s. house tank water, 100 L.s. Stagnant water, and 100 L.s septating water were collected from November 2008 to December 2009. In Al-Mansoria city, Diala Province. Cryptosporidium Oocysts were found in 125 of 400 liters (31.25 %) (table 1), which divided in to 22 liters (22%) of tap water supplies that appear at spring only, This parasite oocysts found in 32 liters (32%) of house tank water which range from 72% in spring to 16% in summer, and they found in 35 liters (35%) and 36 liters (36%) of septating and stagnant water respectively, the highest rates 48% ,of septating water and 60% of stagnant water were shown in spring but the lowerst 24% and 20% in summer respectively (table 2). The prevalence rate varied according to the seasons over the year, this indicates that the seasonal factors may effect on the presence of oocysts (fig.1), with a significant differences (p<0.05).